Zoonotic Brugia pahangi filariasis in a suburbia of Kuala Lumpur City, Malaysia - Tan, L.H.; Fong, M.Y.; Mahmud, R.; Muslim, A.; Lau, Y.L.; Kamarulzaman, A. (Elsevier, 2010)
Five local Malaysian patients with clinical manifestations consistent with lymphatic filariasis were referred to our medical centre between 2003 and 2006. Although no microfilariae (mf) were detected in their nocturnal blood samples, all were diagnosed to have lymphatic filariasis on the basis of clinical findings and positive serology results. PCR on their blood samples revealed that two of the patients were infected with Brugia pahangi, an animal filarial worm hitherto not known to cause human disease in the natural environment. All the patients were successfully treated with anti-filarial drugs: four patients were treated with a combination of diethylcarbamazine (DEC) and albendazole, and one with doxycycline. Four of them were residents of Petaling Jaya, a residential suburbia located 10 km southwest of Kuala Lumpur city, Malaysia. The fifth patient was a frequent visitor of the suburbia. This suburbia has no history or record of B. malayi infection. The most likely vector of the worm was Armigeres subalbatus as extensive entomological surveys within the suburbia revealed only adult females of this mosquito species were infected with B. pahangi larvae. Wild monkeys caught in the suburbia were free from B. pahangi mf, but domestic cats were mf positive. This suggests that infected cats might be the source of the zoonotic infection in the suburbia. (C) 2010 Elsevier Ireland Ltd. All rights reserved.